ChemInform Abstract: Recent Progress Towards Transition Metal‐Catalyzed Direct Conversion of Cellulose to 5‐Hydroxymethylfurfural. Issue 17 (4th April 2013) - Li, Hu; Chang, Fei; Zhang, Yuping; Hu, Deyu; Jin, Linhong; Song, Baoan; Yang, Song
Abstract Review: 108 refs.